2001
DOI: 10.1046/j.1365-2958.2001.02638.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular superoxide production by Enterococcus faecalis requires demethylmenaquinone and is attenuated by functional terminal quinol oxidases

Abstract: SummaryThe intestinal commensal bacterium, Enterococcus faecalis, is unusual among prokaryotic organisms in its ability to produce substantial extracellular superoxide. Transposon mutagenesis, allelic replacement, and electron spin resonance (ESR)-spin trapping showed that superoxide production and generation of derivative hydroxyl radical were dependent on membrane-associated demethylmenaquinone. Extracellular superoxide was generated through univalent reduction of oxygen by reduced demethylmenaquinone. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
115
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(125 citation statements)
references
References 58 publications
1
115
0
3
Order By: Relevance
“…The main sources of ROS in E. faecalis are oxidative metabolism of glycerol and incomplete demethylmenaquinone reduction during the activity of the electron transport chain in the absence of heme (31,32). Since the FMC media lack both glycerol and heme, we speculated that the majority of H 2 O 2 produced under these conditions derives from the incomplete electron transport chain and subsequent superoxide dismutation by MnSOD.…”
Section: Linkage Of (P)ppgpp and Metal Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…The main sources of ROS in E. faecalis are oxidative metabolism of glycerol and incomplete demethylmenaquinone reduction during the activity of the electron transport chain in the absence of heme (31,32). Since the FMC media lack both glycerol and heme, we speculated that the majority of H 2 O 2 produced under these conditions derives from the incomplete electron transport chain and subsequent superoxide dismutation by MnSOD.…”
Section: Linkage Of (P)ppgpp and Metal Homeostasismentioning
confidence: 99%
“…In E. faecalis, lack of (p)ppGpp severely affected the metabolic profile of the cell even in the absence of stress, resulting in a significant decrease in lactate production and a concomitant increase in the levels of formate, ethanol, and acetoin (18). As by-products of its metabolism, E. faecalis releases significant amounts of ROS, including superoxide and H 2 O 2 (31,32). We previously showed that the (p)ppGpp 0 strain produces ϳ5-fold more H 2 O 2 during exponential growth, likely due to the uncontrolled metabolic flux of this strain (18).…”
Section: Linkage Of (P)ppgpp and Metal Homeostasismentioning
confidence: 99%
“…ROS are also produced during bacterial aerobic metabolism 5,6 . It is well established that M. tuberculosis has evolved multiple ways to detoxify RNS and ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, oxidation of Mn(II) to Mn oxides by a common marine bacterium, Roseobacter AzwK-3b, was found to be a consequence of enzymatic extracellular production of O 2 − , which served as the terminal oxidant of Mn(II) (19). Although extracellular superoxide production has been documented in pathogenic bacteria (20) and phytoplankton (21), very little is known about the occurrence of this process in nonpathogenic heterotrophic bacteria. In contrast, production of extracellular superoxide is widespread throughout the fungal kingdom (22), where it is involved in host defense, posttranslational modification of proteins, hyphal branching, cell signaling, and cell differentiation (22,23).…”
mentioning
confidence: 99%